An Interview with Timothy Williamson. - CHEN, BO (Theoria: A Swedish Journal of Philosophy, 2011)
An interview with Timothy Williamson, the Wykeham professor of logic at Oxford University in England, is presented. He talks about his education, his academic career, his main research fields, his family and some of his amateur hobbies. He discusses how his background in mathematics and philosophy and training in computer programming contributed to his philosophical career. Williamson also outlines the important ideas in his book "Identity and Discrimination."